Graphene Nanoplatelets - Suárez, Alberto Jiménez (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Graphene nanoplatelets (GNPs) have attracted considerable interest due to their exceptional mechanical, electrical, and thermal properties, among others. This book provides a deep review of some aspects related to the characterization of GNPs and their applications as nanoreinforcements for different types of matrices such as polymeric- or cement-based matrices. In this book, the reader will find how these nanoparticles could be used for several industrial applications such as energy production and storage or effective barrier coatings, providing a wide overview of future progress in this topic